Measuring Liquidity in Bond Markets - Schestag, Raphael; Schuster, Philipp; Uhrig-Homburg, Marliese (Review of Financial Studies, 2016)
In the literature, there is no consensus on a common approach to measure bond liquidity. This paper is the first to comprehensively compare all commonly employed liquidity measures based on intraday and daily data for the U.S. corporate bond market. We find that high-frequency measures based on intraday data are very strongly correlated, implying that previous results should be robust regarding the chosen measure. Most low-frequency proxies based on daily data generally also measure transaction costs well. However, three proxies clearly take the lead: Corwin and Schultz's (2012) high-low spread estimator, Roll's (1984) measure, and Hasbrouck's (2009) Gibbs measure. Received August 13, 2015; accepted December 5, 2015 by Editor Stefan Nagel.